Evaluating Franz Magnis-Suseno’s Argument for God's Existence: A Systemic Philosophical Approach - Gigih Saputra; M. Rodinal Khair (Digital Press Social Sciences and Humanities)
The discourse on the argument for God's existence is one of the philosophical themes in Indonesia, with one of the prominent figures Franz Magnis Suseno. This research is based on a gap in the absence of an in-depthstudy with a new perspective on Magnis's thought. This research aims to provide new insights through a critique and recommendations on Magnis's views concerning cosmological and teleological arguments. The author introduces a new perspective, namely the Cosmo-Teleological System Theory and the Systematic Critique of Atheism Theory. The findings of research about the ambiguity of the deepest nature of causality, the lack of integration between cosmological and teleological arguments, and the insufficient depth in arguments to ascertain the limits beyond the natural world, particularly regarding the possibility of immaterial causal chains in the origins of the universe. Another gap identified is the notion that the Absolute does not necessarily imply God, which can lead to the implication that the Absolute could be something other than God. Magnis's views on teleological argument, specifically the inconsistency in the use of principles of directionality and randomness. Magnis still permits randomness, given the possibility of Multiverses, and posits that our universe might be the result of a random combination of these Multiverses. Orderliness presupposes a final purpose, whereas randomness does not. Absence of purpose results in the lack of unified direction among the components of a system, which in turn leads to the absence of a cyclical pattern, a hallmark of an orderly system, leaving only chaos.